Building Mosque-Based Food Self-Sufficiency Through Paddy Infaq - Azis Muslim; Febri Mardhiatus Sa’diyah (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
The essence of empowerment was to build community’s consciousness of recognizing the existing potency and to utilize such potency to deal with the problems encountered. Therefore, community empowerment is highly determined by the community itself, rather than by outsiders facilitating. This research aimed to describe concept, implementation, and output of food self-sufficiency development conducted by Geneng Hamlet people in Jambakan Village of Bayat Sub District of Klaten Regency in solving the problem faced. The research was conducted using qualitative approach. Data was explored using observation, in-depth interview, and documentation. Data analysis was conducted using an interactive technique. The result of research showed that the concept of dealing with food vulnerability during dry season was designed by submitting infaq to Al-Ikhlas mosque in the form of dry rice in each of harvest seasons. In implementation domain, this collected infaq was managed professionally through rice barn (lumbung) to be distributed to its jamaah (community) in the form of loan and sympathetic care. The output was very positive as it could suffice the need for food during dry season, people can access the resource needed, and rice barn could help the weak group and the meritorious people in Geneng Hamlet.